The Use of Multimedia in Increasing the Learning Motivation of Students in Senior High Schools - Asril, Zainal; Satrial, Ardi; Pane, Syahrani Surti; Fatimah, Fatimah; Pane, Mayang Surti (Khalaqa: Journal of Education and Learning, 2024)
Teachers must also be creative in preparing media and learning facilities to deliver their students to become intelligent human beings, creative, and have strong diversity integrity. This study aims to find out the types, steps, and factors that affect learning media in increasing student learning motivation in fiqh learning in high school. This research uses a qualitative method, the type of research is descriptive, the data collection technique is field study and literature study, and the data analysis technique used is through interviews, documentation, and observation, with the research location at the Upper Secondary School. Results of the study: 1. The types of Learning Media used by Fiqh Teachers are: photos, concept maps, posters, Voice Recordings, Radio, learning videos, Textbooks, LKS, WhatsApp, Youtube, Google; powerpoint, Dolls, Whiteboards, 2. Steps for Fiqh teachers to use Learning Media: Preparation, b. Implementation/presentation 3. Follow-up, c) Supporting factors for media selection: a) the existence of teachers' competence and skills in using media so that teachers understand the characteristics of each media, b) availability of funds in media procurement, c) availability and ease of obtaining media d) the existence of flexibility and comfort of media e) the existence of support from the school, especially the principal, The factors that inhibit the selection of media include a) the availability of time in using it b) school facilities that inadequate c) the situation and conditions of the school environment are not supportive.